Evaluating Holistic Education and Digital Learning model for advancing SDG4: a longitudinal mixed-effects modeling approach - Prema Nedungadi; Radhika Menon; Georg Gutjahr; Raghu Raman (Cogent Social Sciences)
This longitudinal study evaluates the Holistic Education and Digital Learning (HEDL) model within rural Indian contexts, contributing to United Nations Sustainable Development Goal 4 (SDG4). The holistic education includes activities such as yoga, environmental activities, cultural programs, cleanliness drives and substance abuse ambassador programs while the digital learning encompasses applications for language learning, numeracy, touch writing and vocabulary enhancement. The dataset comprises 8869 students from 78 HEDL centers across 21 Indian states, monitored over 5 years through standardized assessments, attendance metrics and digital teacher supervision. Employing mixed-effects models with nested random effects for centers and students, the findings indicate that the HEDL model significantly elevates literacy and language skills in these settings. The digital learning component alone contributes to a 0.5% average weekly literacy gain. Furthermore, the holistic educational components demonstrate a statistically significant correlation with improved literacy outcomes: a 25% increased likelihood of achieving grade-level reading and a 63% increased likelihood of attaining grade-level writing. The results are found to be reliable and robust across time and a large number of locations across India. The results contribute to understanding the dual role of blended learning and holistic education in rural education and underscore the potential of such pedagogical models.